Middle meningeal artery embolization for chronic subdural hematoma: Interpreting divergent randomized evidence and guiding patient selection - Dongfang Yang; Haibin Zhang; Ji Xia; Baoling Liu; Mei Li (Frontiers in Neurology, 2026)
Chronic subdural hematoma (cSDH) is among the most common neurosurgical conditions in adults, with incidence rising steadily in aging populations and with increasing antithrombotic drug use. Burr-hole drainage remains the standard treatment for symptomatic cSDH; however, postoperative recurrence rates range from 8 to 30%. Middle meningeal artery embolization (MMAE) targets the pathological blood supply of the dural neomembrane, intervening at the biological source of hematoma progression and representing a fundamental shift in cSDH management. Between 2024 and 2025, four landmark randomized controlled trials (RCTs)—EMBOLISE, STEM, MAGIC-MT, and EMPROTECT—were published. Their conclusions diverge: EMBOLISE and STEM demonstrated that MMAE significantly reduced treatment failure, whereas MAGIC-MT ( p = 0.10) and EMPROTECT ( p = 0.13) did not reach statistical significance on their primary endpoints, despite point estimates consistently favoring MMAE. Unlike published meta-analyses that address the question of whether MMAE is effective overall by pooling effect sizes, this review systematically examines potential sources of heterogeneity across the four RCTs—including primary endpoint definitions, patient population characteristics, embolic materials and technical strategies, the differential impact of open-label design on bias, and embolization timing. Throughout the manuscript, we distinguish three levels of evidence: conclusions directly supported by randomized data (Level A), inferences derived from non-randomized subgroup or indirect comparisons (Level B), and hypotheses grounded in biological reasoning (Level C). On this basis, we propose a multidimensional patient stratification framework incorporating age, antithrombotic status, angiographic classification, and hematoma characteristics, with each recommendation explicitly graded by level of evidence. We emphasize that this framework has not been prospectively validated and is intended exclusively to generate hypotheses for future clinical research, not to serve as a treatment guideline. We further delineate the current clinical indications for MMAE, provide a systematic summary of its complications and safety profile, and identify critical future directions including individual patient data meta-analysis, standardized outcome definitions, and prospective biomarker- and imaging-based validation studies.